(untitled) (Research, Society and Development, 2020)
Anxiety and depression are increasingly prevalent mental illnesses in the world that provide quality of life for patients. Although medication is considered the first line of intervention, many do not have good adherence to treatment. Nutritional monitoring and phytotherapy appear as a therapeutic resource to improve symptoms and promote the health of these pathologies. This study aimed to understand, through a literature review, the role of food and herbal medicine in the treatment of anxiety and depression disorders in the adult and elderly population. For bibliographic research, the PubMed, SciELO, ClinicalKey and CAPES database was used with the selection of articles published in national and international journals, from 2010 to 2020. It was found that the quality of the diet affects the general clinical status of the patient and contributes in an impactful way in improving the health of the studied pathologies. The example of supplementing micronutrients such as zinc, magnesium, vitamins A, C, D, E and B complex was highlighted, as well as including food sources containing tryptophan and omega 3 for a beneficial response in the profile of anxiety and depression. Thus, nutritional care is indicated, since the evidence points to a direct relationship between good nutrition and mental health.